Case Report: A novel FGFR1 fusion in acute B-lymphoblastic leukemia identified by RNA sequencing - Zhang, Zhibo; Zhu, Yiyan; Wang, Zheng; Zeng, Zhao; Wen, Lijun; Zhang, Ling; Chen, Suning (Frontiers in Oncology, 2023)
8p11 myeloproliferative syndrome is a rare hematological malignancy with aggressive course caused by the various translocation of FGFR1. In this study, a novel FGFR1 fusion was identified by RNA sequencing in a 28-year-old male patient with acute B-lymphoblastic leukemia. The patient harbors an in-frame fusion between KIF5B exon 15 and FGFR1 exon 10. The FGFR1 fusion and its protein expression was validated by Sanger sequencing and Western blot. Meanwhile, cytogenetic analysis reported a normal karyotype and targeted DNA sequencing identified no driver mutations, respectively. Despite he achieved complete remission after induction regimen, a relapse occurred and he became refractory to chemotherapy, and salvage haploidentical hematopoietic stem cell transplantation failed to control the progressive disease. In conclusion, we present the first case of KIF5B-FGFR1 fusion in hematological malignancy. These findings extend the spectrum of translocation in 8p11 myeloproliferative syndrome, and demonstrate the great prospect of RNA sequencing in clinical practice again.